Prevalence and Associated Factors of Caregiver Burden among Stroke Patients - Poovatanaruk, Niracha; Nakawiro, Pakkawee (Journal of Preventive Medicine Association of Thailand, 2020)
Stroke is the one of the leading cause of death and long-term disability globally. Stroke patients may lose the ability to do daily activities and rely on their caregivers in the long run, so caregivers play an essential role which is a high burden. Stroke survivors’ care is a matter of enduring stress, leads to physical, psychological, social, financial burden including quality of life. This cross-sectional study aimed to survey the prevalence and associated factors of caregiver burden in 66 caregivers of stroke patients in Phra Nakhon Si Ayutthaya city municipality between October to December 2019. Data were collected by interview using standardized questionnaires. The questionnaires consisted of caregiver and stroke patient information and Zarit burden interview. The data were reported as frequency and percentage and were analyzed by chi square test with statistic significant level at 0.05. The prevalence of caregiver burden was 40.9% and factors related to caregiver burden included household monthly income 0-5000 Baht (p=0.041), concern about the expense (p=0.014) and low Barthel index scale (p=0.008). Family caregivers reduced the feeling of caregiver burden. Therefore, health care providers should collaborate all stakeholders to promote work to increase household income, explore resources to reduce family’s expense and support the family members to be caregivers to improve caregiver’s quality of life.